REGIONAL POLICY AND SUPPORT OF REGIONAL DEVELOPMENT: COMPARISON OF GERMAN, THE EU, AND UKRAINIAN EXPERIENCE - Melnyk, Alla (Journal of European Economy, 2018)
The problems of the theory of regional policy which are related to the globalization processes and the European Union enlargement are discussed, the experience of regional development support in Germany and the European Union is characterized, the regional policy in the EU and in the candidate countries is discussed. Preconditions of building up of current regional policy and the policy of support of regions in Ukraine are systematized. Urgent problems in this area are determined, and the ways to meet these challenges in the context of the EU and German experience are shown.